Thiol-Disulfide Homeostasis in Noise-Induced Hearing Loss in Rats - Enes Aydın; Serpil Mungan Durankaya; Osman Yilmaz; Günay Kirkim; Safiye Aktaş; Salim Neşelioğlu; Özcan Erel; Yüksel Olgun; Abdullah Dalgıç (Journal of International Advanced Otology)
Background: This study was designed to assess if thiol-disulfide homeostasis could be used as diagnostic biomarker in noise-induced hearing loss (NIHL) in a laboratory animal model.